Intraoperative Fluorescence Imaging During Robotic Pancreatoduodenectomy to Detect Suture-Induced Hypoperfusion of the Pancreatic Stump as a Predictor of Postoperative Pancreatic Fistula (FLUOPAN): Prospective Proof-of-concept Study - Jeffrey W. Chen; Sanne Lof; Maurice J. W. Zwart; Olivier R. Busch; Freek Daams; Sebastiaan Festen; Zhi Ven Fong; Melissa E. Hogg; Maxime D. Slooter; Els J.M. Nieveen van Dijkum; Marc G. Besselink; for HPB-Amsterdam (Annals of Surgery Open)
Background:. A potential downside of robotic pancreatoduodenectomy (RPD) is the lack of tactile feedback when tying sutures, which could be especially perilous during pancreatic anastomosis. Near-infrared fluorescence imaging with indocyanine green (NIRF-ICG) could detect transpancreatic-suture-induced hypoperfusion of the pancreatic stump during RPD, which may be related to postoperative pancreatic fistula (POPF) grade B/C, but studies are lacking. Methods:. This prospective study included 37 patients undergoing RPD to assess the relation between pancreatic stump hypoperfusion as objectified with NIRF-ICG using Firefly and the rate of POPF grade B/C. In 27 patients, NIRF-ICG was performed after tying down the transpancreatic U-sutures. In 10 ‘negative control’ patients, NIRF-ICG was performed before tying these sutures. Results:. Pancreatic stump hypoperfusion was detected using NIRF-ICG in 9/27 patients (33%) during RPD. Hypoperfusion was associated with POPF grade B/C (67% [6/9 patients] versus 17% [3/18 patients], P = 0.026). No hypoperfusion was objectified in 10 ‘negative controls’. Conclusions:. Transpancreatic-suture-induced pancreatic stump hypoperfusion can be detected using NIRF-ICG during RPD and was associated with POPF grade B/C. Surgeons could use NIRF-ICG to adapt their suturing approach during robotic pancreatico-jejunostomy. Further larger prospective studies are needed to validate the association between transpancreatic-suture-induced hypoperfusion and POPF.